Association between macrophage migration inhibitory factor gene and growth differentiation factor 15 gene polymorphisms and circulating levels with respiratory distress syndrome among preterm neonates - Bakri, Ali Helmi; Hassan, Mohammed H.; Abd-Elbaseer, Khaled Abdalla; Sayed, Mahmoud Abo -Alhassan; Abdallah, Ahmed Alamir Mahmoud; Abd-Elmawgood, Eman Ahmed (Clinical and experimental pediatrics, 2025)
In preterm newborns, neonatal respiratory distress syndrome (RDS) is among the main causes of respiratory failure and mortality. However, the effect of macrophage migration inhibitory factor (MIF) on neonatal developmental lung disease is not well documented in the literature. Moreover, little is known about the effects of growth differentiation factor-15 (GDF-15) on lung maturity in preterm infants. To evaluate serum MIF and GDF-15 levels in preterm infants with and without RDS and analyze the genetic profile of single nucleotide polymorphisms (SNPs) for MIF rs755622 G>C and GDF-15 rs4808793 C>G. In this case-control study, 90 preterm newborns were categorized into three groups: group A included 30 preterm newborns with mild-to-moderate RDS, group B included 30 preterm newborns with severe RDS, and group C included 30 healthy preterm newborns. Enzyme-linked immunosorbent assay methods were used to measure serum MIF and GDF-15 levels. The MIF rs755622 G>C and GDF-15 rs4808793 C>G SNPs were analyzed by restriction fragment length polymorphism-polymerase chain reaction. Significantly higher median MIF and GDF-15 blood levels were noted among neonates with severe RDS (17.32 µg/L and 3.19 pg/mL, respectively) versus those with mild to moderate RDS (5.5 µg/L and 0.71 pg/mL, respectively) (p <0.05 for both). A significantly higher frequency of a mutant C-allele of MIF rs755622 G>C was noted among cases (37.5%) versus controls (13.3%) (p=0.001; odds ratio, 0.256; 95% confidence interval, 0.112-0.589). A significantly higher frequency of a mutant G-allele of GDF-15 rs4808793 C>G SNPs was noted among cases (49.2%) versus controls (30%) (odds ratio, 0.443; 95% confidence interval, 0.229-0.856). These findings suggest that serum MIF and GDF-15 levels are strongly associated with RDS severity among preterm neonates. Moreover, polymorphisms of MIF and GDF-15 could be genetic risk factors for the development of neonatal RDS among preterm babies.